ANALISIS KESULITAN BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA KELAS III DI SEKOLAH DASAR - Siti Halimah; Adrias, Adrias; Aissy Putri Zulkarnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
At SDN 06 Kp Lapai, third-grade students face a variety of challenges in learning mathematics that need to be recognized and addressed. The purpose of this study is to identify these difficulties and recommend appropriate solutions. A qualitative approach was used, with teacher interviews as the main source of data. The results highlighted several key issues. First, students often struggle to understand word problems and to apply the correct formulas. Second, the complexity and unclear nature of some word problems confuse students, which results in a lack of motivation to complete the tasks. Furthermore, students tend to lose interest quickly when faced with long and difficult problems, making them uncertain about how to solve the mathematical questions. To overcome these challenges, it is recommended that teaching methods and materials be adapted to better suit students' needs. This could include using more engaging and interactive teaching techniques and diversifying teaching resources. Continuous evaluation and revision of the curriculum are also necessary to ensure its effectiveness. Additionally, collaboration between teachers and parents is crucial to improving the overall quality of mathematics education at SDN 06 Kp Lapai.